Pengaruh Pengalaman Berwisata terhadap Kepuasan Wisatawan di Daya Tarik Wisata Atlantis Land Surabaya - Nadya Rezita Putri; Joko Mijiarto (Jurnal Ragam Pengabdian, 2026)
This study examines the effects of tourism experience dimensions—hedonism, novelty, local culture, refreshment, meaningfulness, involvement, and knowledge—on tourist satisfaction. The research addresses a gap in the literature, as limited studies have simultaneously investigated multiple dimensions of tourism experience, particularly within the context of artificial tourist attractions. The study focuses on tourists who visited Atlantis Land Surabaya in 2025. This study highlights the need to improve the management of Atlantis Land Surabaya in order to strengthen its image and enhance the tourism competitiveness of Surabaya. A quantitative approach was employed, with data collected through structured questionnaires and analyzed using SPSS version 27. The findings reveal that, collectively, all dimensions of tourism experience significantly influence tourist satisfaction. However, at the individual level, not all variables demonstrate significant effects. These findings underscore the importance of enhancing tourism experiences by fostering innovation and creating more interactive and integrated offerings. Strengthening these aspects is essential to improving overall tourist satisfaction and ensuring the competitiveness of the tourist attraction